Self-repairing high polymer grouting material for dam leakage disposal and dam leakage disposal method

By using the isocyanate polar groups in the self-healing polymer grouting material to form a three-dimensional network structure after cracking, the problem of easy re-leakage of dam seepage materials is solved, realizing the material's self-repair and long-term leak-stopping effect, adapting to base deformation, and reducing maintenance costs.

CN120904703APending Publication Date: 2025-11-07上海豫宏(金湖)防水科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511412649.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing dam seepage materials are prone to re-leakage in loose soil or frequently vibrating foundations. Furthermore, inorganic materials have poor fluidity and low bonding strength, making them unable to adapt to base deformation and lacking self-healing capabilities, resulting in high maintenance costs and poor performance.

Method used

The self-healing polymer grouting material consists of component A resin and component B. It utilizes the polar isocyanate groups to react with water after the material cracks to form a three-dimensional network structure, thereby achieving self-healing. Combined with a catalyst to control the reaction rate, a stable cross-linked network is formed.

Benefits of technology

The material can self-repair after cracking, reduce the re-leakage rate, improve the deformation resistance, reduce environmental pollution, has excellent bonding performance and long-lasting leak-stopping effect, adapts to base layer deformation, is resistant to high temperature and aging, and has good water flow blocking performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a dam leakage disposal self-repairing high polymer grouting material and a dam leakage disposal method, and belongs to the technical field of grouting repair, the dam leakage disposal self-repairing high polymer grouting material comprises a component A resin and a component B; the component A is prepared from the following components in parts by mass: 40 to 60 parts of asphalt, 10 to 20 parts of aromatic hydrocarbon oil for environment-friendly rubber, 8 to 20 parts of rosin polyester polyol, 20 to 40 parts of polyphenylmethane polyisocyanate, 0.1 to 1 part of a catalyst and 5 to 15 parts of an auxiliary agent; the component B is a curing agent; the component A resin also comprises 1.5 to 6.5 parts by weight of isocyanate polar groups; the non-cured rubber asphalt waterproof material disclosed by the invention has excellent self-healing property, adhesive property and wet base layer constructability of a non-cured rubber asphalt waterproof material; the adhesive contains isocyanate polar groups, can form chemical linkage with the surfaces of base materials such as sandy soil, concrete, rock soil and the like, and has a better bonding effect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of grouting repair, and particularly relates to a dam leakage treatment self-repairing high polymer grouting material and a dam leakage treatment method. BACKGROUND

[0002] Water conservancy infrastructure is an important cornerstone for water safety, and at present, various reservoirs and embankments have been built in China; however, with the factors of natural aging, geological changes, water erosion and the like after long-term operation, water conservancy facilities are in a dangerous situation, and leakage is one of the most important diseases; At present, in order to solve the leakage of embankments, a leakage stopping material is mainly used for grouting leakage stopping, and mainstream grouting materials in the prior art include two types of organic materials (such as polyurethane, epoxy, acrylic acid and the like) and inorganic materials (such as cement-based materials), but the two types of materials still have certain deficiencies in daily use: Organic materials: although they have good permeability and leakage stopping effect (such as polyurethane can form a closed-cell foam), but in loose soil or frequently vibrating ground, new cracks are easily generated due to structural deformation, resulting in a high re-leakage rate; and the diluent added to improve the permeability does not participate in the reaction, and is easy to separate out, causing environmental pollution.

[0003] Inorganic materials: although cement-based materials are convenient to obtain and low in cost, they have poor fluidity, are easy to be diluted by water, have low cementing strength and the like, and have limited leakage stopping effect, and cannot adapt to the deformation of the base, and are difficult to solve the long-term leakage problem.

[0004] And the materials in the prior art generally lack self-repairing capability: when the materials crack due to disturbance, aging and the like, they cannot restore the sealing property by themselves, and need to rely on secondary construction, which not only increases the maintenance cost, but also may expand the danger due to untimely treatment, so a grouting material with excellent leakage stopping performance, strong adhesion, anti-deformation capability and self-repairing function is particularly important. SUMMARY

[0005] In view of the problems in the prior art, the application provides a dam leakage treatment self-repairing high polymer grouting material and a dam leakage treatment method.

[0006] To solve the above problems, the application adopts the following technical solutions.

[0007] The dam seepage treatment self-repairing polymer grouting material comprises an A component resin and a B component; the A component comprises, in terms of mass, 40-60 parts of asphalt, 10-20 parts of aromatic oil for environment-friendly rubber, 8-20 parts of rosin polyester polyol, 20-40 parts of polyphenylmethane polyisocyanate, 0.1-1 part of catalyst, and 5-15 parts of additive; the B component is a curing agent; the A component resin further comprises 1.5-6.5 parts of isocyanate polar groups; when the material is cracked by disturbance, the exposed isocyanate polar groups in the A component can undergo a curing reaction with water and self-polymerize to form a three-dimensional network structure, thereby realizing continuous self-repairing plugging.

[0008] Preferably, the preparation steps of the A component resin comprise: Step S1, the asphalt and the aromatic oil for environment-friendly rubber are added to a clean vacuum reaction kettle, heated to 120℃, vacuumized for 2h, and the moisture in the reaction kettle is removed; when the moisture reaches below 0.001%, the vacuumization is stopped; Step S2, the reaction kettle is cooled to 80℃, and then the rosin polyester polyol and the polyphenylmethane polyisocyanate are added to the reaction kettle and fully stirred to be uniform; Step S3, the catalyst is gradually added to the reaction kettle using a peristaltic pump, and the additive is added at the same time, and the temperature is kept at 80℃; then the reaction is carried out for 2h under stirring to form a repair product, Step S4, the repair product is packaged and stored under nitrogen condition.

[0009] Further, the catalyst is dibutyltin dilaurate.

[0010] Further, the curing agent is a trimerization catalyst.

[0011] Further, the asphalt has a penetration of (100g, 5s, 0℃) 180-280 (0.1mm), a softening point ≥ 17℃, and a flash point ≥ 210℃.

[0012] Further, the aromatic oil for environment-friendly rubber has an open flash point ≥ 200℃, an aromatic hydrocarbon content > 84%, and a pour point ≥ 10℃.

[0013] Further, the rosin polyester polyol has a hydroxyl value of 350-450mgKOH / g and a viscosity of 5000-12000mPa·s.

[0014] Further, the mass ratio of the A component resin to the B component is 100:0.05-0.1.

[0015] The dam seepage treatment method adopts the self-repairing polymer grouting material, and the steps are as follows: Step one, put the resin of A component into the batching tank, and heat to 120℃, then add B component into the batching tank, after mixing by stirring, the repairing liquid is obtained; Step two, use the grouting machine to inject the mixed repairing liquid of step one into the concrete crack.

[0016] Compared with the prior art, the beneficial effects of the present application are: 1. The present application has excellent self-healing property, bonding property and moisture base layer workability of non-solidified rubber asphalt waterproof material; 2. The present application contains isocyanate polar groups inside, which can form chemical links with the surface of base materials such as sand, concrete and rock soil, and has better bonding effect; 3. When the material is disturbed, deformed and cracked, the isocyanate polar groups in the present application are exposed from the material body, which not only reacts with water, but also trimerizes the isocyanate polar groups themselves to form a three-dimensional network structure, so that the material is re-crosslinked and continuously plays the plugging effect; 4. The three-dimensional network polymer resin skeleton contained in the material of the present application also makes the grouting material have excellent anti-cracking performance, high temperature resistance, aging resistance, acid and alkali corrosion resistance and other excellent properties, and has good water flow sealing effect. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical scheme and advantages of the embodiments of the present application more clear, the technical scheme in the embodiments of the present application will be described clearly and completely below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application.

[0018] Embodiment 1: In the prior art, water conservancy infrastructure is prone to leakage after long-term operation due to natural aging, geological changes and other factors. The traditional grouting material has obvious defects: organic material is easy to re-leak due to structural deformation in loose soil, and the diluent is precipitated to pollute the environment; inorganic material has poor fluidity and low cementing strength, and cannot adapt to base deformation; the existing materials generally lack self-repairing ability, and need secondary construction and maintenance after cracking, which is high in cost.

[0019] In order to solve the above problems, by analyzing the failure mechanism of the existing material, it is found that simply improving the initial bonding strength cannot solve the re-leakage problem under dynamic deformation, and a repair factor that can be activated needs to be pre-set in the material. Based on the polyurethane reaction mechanism, it is tried to reserve unreacted active groups in the prepolymer, so that it can trigger secondary curing with the environment after cracking.

[0020] A component resin and B component, wherein the A component resin raw materials: low viscosity flexible asphalt W200: 400 kg; aromatic hydrocarbon oil for environmental protection rubber: 150 kg; rosin polyester polyol JC-380: 150 kg; wanenate PM200 of Wanhua Chemical Group Co., Ltd.: 200 kg; dibutyltin dilaurate: 1 kg; auxiliary agent: 99 kg; B component curing agent: trimerization catalyst.

[0021] 400k low viscosity flexible asphalt W200 and 150kg aromatic hydrocarbon oil for environmental protection rubber are added to a clean vacuum reaction kettle, heated to 120℃, vacuumed for 2h, and the water inside is removed, when the water content is below 0.1%, stop vacuuming; Specifically, the asphalt and aromatic hydrocarbon oil form a flexible continuous phase, the hydroxyl groups in the rosin polyester polyol and isocyanate undergo polycondensation to form a polyurethane prepolymer. The catalyst accelerates the reaction to form an initial crosslinked structure, while retaining some unreacted isocyanate groups by controlling the reaction degree. When the material cracks under external force, the newly exposed isocyanate polar groups on the crack surface undergo secondary crosslinking with the hydroxyl groups in the leakage water, and self-polymerize to form a three-dimensional network to fill the cracks. The curing agent B component promotes rapid setting of the material after grouting, while not affecting the reserved active groups.

[0022] The application realizes the self-repairing function after the material cracks, effectively reduces the re-leakage rate; the flexible network structure improves the anti-deformation ability and adapts to the stress change of loose foundation; no diluent is used, reducing environmental pollution; the reserved active groups can trigger the repair reaction multiple times at different time points, prolonging the service life of the material.

[0023] Cool to 80℃, add 150kg rosin polyester polyol JC-380, 200kg polyphenylmethane polyisocyanate wanenate PM200, and mix thoroughly; Add 1kg of catalyst dibutyltin dilaurate and 99kg of other auxiliary agents gradually with a peristaltic pump, keep the temperature at 80℃, then fully react under stirring for 2h to form the final product, and store it under nitrogen.

[0024] In a specific implementation, first, the prepared A component resin is heated to 120°C, then mixed with the B component curing agent in a ratio of 100:0.05-0.1 by mass, and then injected into the silo of the grouting equipment. Then, the caterpillar hydraulic trenching machine is used to vibrate (static pressure) and composite the trench on the earth dam. At the same time, the grouting machine is used to synchronously lift the grouting. The construction process is as follows: material A / B component pre-mixing → arranging trench hole position → vibrating (static pressure) and composite trench → synchronously lifting grouting to form the first width of the high polymer flexible anti-seepage wall → hole setting vibrating (static pressure) and composite trench → synchronously lifting grouting to form the second width of the high polymer flexible anti-seepage wall → … → hole sealing → forming a continuous lap joint anti-seepage wall.

[0025] Specifically, in the preparation process, first, through heating at 120°C and the synergistic effect of vacuum negative pressure, the water content of the reaction system is reduced to below 0.1%. The possibility of side reaction between the isocyanate component and water in the prepolymerization stage is eliminated. Then, the temperature is accurately controlled at 80°C. The activation energy required for the prepolymerization reaction of the rosin polyester polyol and the polyphenylmethane polyisocyanate is met, and the decomposition of the polyol at high temperature to produce byproducts is avoided. The catalyst and the additive are injected at a constant flow rate by using a peristaltic pump, and the reactants are fully contacted by using continuous mechanical stirring, so as to ensure that the isocyanate polar groups are uniformly distributed in the resin system. Finally, under the protection of nitrogen, the material is sealed and packaged, which effectively blocks the contact between the isocyanate groups and the moisture and oxygen in the environment during storage, and maintains the self-repairing activity of the material.

[0026] Through the above technical solution, the present application realizes the full reaction and stable storage of the key components in the preparation process of the grouting material, and ensures that the isocyanate groups can effectively trigger the self-repairing reaction in the subsequent leakage treatment. The accurate control of the preparation process makes the resin system form a stable isocyanate distribution state. When the material is cracked by external force, the exposed active groups can quickly react with water to form a three-dimensional network structure, continuously repair the cracks and restore the sealing performance.

[0027] In the static pressure trenching stage, the caterpillar hydraulic trenching machine presses the specially designed trenching plate grouting drill down into the dam body to form a grouting trench hole with a certain depth and very small thickness. The drill used in the grouting process is composed of a hole setting pipe, a grouting pipe, a tunneling head and a slurry isolation pipe. The hole setting pipe is used to ensure that the high polymer sheet structure formed by two adjacent grouting can achieve good lap joint effect. The grouting pipe is used to inject high polymer slurry into the trench hole. The tunneling head is used to dig down the soil to form the grouting trench. The slurry isolation pipe and the hole setting pipe have the same diameter, and the purpose is to form a trench hole matched with the hole setting pipe and ensure that no slurry is injected to form an empty trench as a hole setting trench for the next grouting, so as to ensure that two high polymer sheet structures are lap jointed to form a wall.

[0028] The lifting grouting stage is that when the drilling tool is pressed to the predetermined depth, the polymer slurry is injected into the slot hole from the grouting pipe, and at this time the grouting drilling tool is lifted upward. During the lifting process, the polymer slurry fills the grouting slot and the hole slot formed by the sleeve pipe. During the lifting process, the slurry isolation pipe is not lifted, and remains in the original state until the drilling tool is lifted to the top and the polymer in the slot is completely filled, and then it can be taken out of the soil, so as to ensure that the hole slot formed by the slurry isolation pipe is completely free of injected polymer slurry.

[0029] After the grouting of one grouting slot hole is completed, the slotting machine is moved forward by a certain distance to excavate the next grouting slot hole. During the excavation process, it is necessary to ensure that the sleeve pipe of the drilling tool is inserted into the empty slot formed by the slurry isolation pipe during the previous slotting. When the drilling tool reaches the predetermined depth, the drilling tool is lifted and grouted according to the same method as the second step described above. Similarly, after the slurry solidifies, the slurry isolation pipe is taken out of the soil. This process is called sleeve connection, and the purpose is to make the adjacent two polymer sheets form a continuous overlapped polymer sheet structure to ensure the continuity of the cutoff wall.

[0030] The performance parameters of the grouting material are as follows in Table 1: No. Item Unit Technical Index 1 Isocyanate polar group content % 1.9 2 Flash point ℃ ≥200 3 Self-healing - No water penetration 4 Water resistance / 1.0 MPa - No water channeling 5 Heat resistance - No dripping at 75℃ 6 Adhesion performance / dry substrate - 100% cohesive failure 7 Adhesion performance / wet substrate - 100% cohesive failure 8 Stress relaxation / no treatment % ≤25% 9 Stress relaxation / heat aging (70℃, 168h) % ≤30% Table 1

[0031] Example 2: A dam leakage treatment self-repairing polymer grouting material, comprising: a component resin and a component B, wherein, A component resin raw materials: Low viscosity flexible asphalt W200: 500 kg; Aromatic oil for environmental protection rubber: 100 kg; Rosin polyester polyol JC-380: 80 kg; Wan Hua Chemical Group Co., Ltd. wanenate PM200: 270 kg; Dibutyltin dilaurate: 1 kg; Auxiliary agent: 49 kg; B component curing agent: trimerization catalyst; Preparation process 500k low viscosity flexible asphalt W200 and 100kg aromatic oil for environmental protection rubber are added to a clean vacuum reaction kettle, heated to 120℃, vacuumed for 2h, and the water content is removed. When the water content is below one thousandth, stop vacuuming; Cool to 80℃, add 80kg rosin polyester polyol JC-380, 270kg polyphenylmethane polyisocyanate wanenate PM200, and mix thoroughly; The dibutyl tin dimethoxide catalyst is added gradually by using a peristaltic pump, while 49 kg of other additives are added, and the temperature is kept at 80°C. Then, under stirring, the reaction is carried out for 2 hours to form the final product, which is then packaged and stored under nitrogen.

[0032] Specifically, in the preparation of the A component resin, the dibutyl tin dimethoxide is uniformly dispersed in the continuous phase composed of asphalt and aromatic oil. When the polyphenylmethane polyisocyanate is mixed with the rosin polyester polyol, the catalyst promotes the rapid formation of urethane bonds between the isocyanate groups and the hydroxyl groups, achieving the stereoscopic crosslinking of the molecular chains. During the reaction process, the coordination of the catalyst can accurately control the reaction rate, avoiding phase separation or bubble generation caused by local excessive heat release. After the material is cured, the catalyst exists in the three-dimensional network structure in the form of a chemical bond and will not affect the self-repairing function due to migration or precipitation.

[0033] Through the above technical solution, the present application realizes the efficient directional reaction of isocyanate and polyol, reduces the interference of by-products on the self-repairing ability of the material, and ensures that the network structure after curing has stable chemical crosslinking points. The low migration property of the catalyst avoids the loss of active ingredients during storage, ensuring the long-term plugging performance of the grouting material under complex geological conditions.

[0034] Specifically, the trimerization catalyst catalyzes the polycondensation reaction between the isocyanate groups and the polyol during the curing stage of the material, forming an initial crosslinked network. When the isocyanate groups are exposed due to the cracking of the material caused by external forces, the residual catalyst activity can continue to catalyze the reaction between the isocyanate and water, promoting the self-polymerization to form a more compact three-dimensional network structure. This dual catalytic mechanism not only ensures the controllability of the initial curing rate, but also realizes the self-repairing function of the damaged part.

[0035] Through the above technical solution, the present application realizes the accurate regulation of the curing rate of the grouting material, avoiding the problems of decreased permeability caused by too fast reaction or plugging failure caused by too slow reaction. At the same time, through the stable crosslinked network of isocyanurate structure and the continuous action of the catalyst, the durability of the plugging effect is significantly improved, effectively inhibiting the re-leakage phenomenon.

[0036] In specific implementation, first, the prepared A component resin is heated to 120°C, then pre-mixed with the B component curing agent in a proportion of 100:0.05-0.1 by mass, and then injected into the grouting equipment bin. Then the process is as follows: 1. Use a drill to drill grouting holes near the cracks of the concrete dam, with multiple grouting holes evenly arranged along the cracks on both sides, and the drilling depth should penetrate the crack; 2. Pre-bury the grouting head at the drilled hole; 3. Connect the grouting pipe of the grouting machine to the grouting head; 4. Start grouting, and change the hole when the grouting liquid is found to overflow from the crack; 5. Remove the grouting head after the grouting is completed; 6. Seal the hole.

[0037] The performance parameters of the grouting material are as shown in Table 2: No. Item Unit Technical Index 1 Isocyanate polar group content % 6.1 2 Flash point ℃ ≥200 3 Self-healing - No water penetration 4 Water resistance / 1.0 MPa - No water channeling 5 Heat resistance - No dripping at 85℃ 6 Adhesion performance / dry substrate - 100% cohesive failure 7 Adhesion performance / wet substrate - 100% cohesive failure 8 Stress relaxation / no treatment % ≤20% 9 Stress relaxation / heat aging (70℃, 168h) % ≤25% Table 2 In summary, the grouting material in the application has the following advantages: The application has excellent self-healing property, bonding property and moisture base layer workability of the non-cured rubber asphalt waterproof material. The application contains isocyanate polar groups, which can form chemical links with the surface of base materials such as sand, concrete and rock soil, and has better bonding effect. When the material is disturbed, deformed and cracked, the isocyanate polar groups in the application are exposed from the material body, which not only has a curing reaction with water, but also has a trimerization reaction, forming a three-dimensional network structure, so that the material is re-crosslinked and continuously plays a plugging effect. The three-dimensional network polymer resin skeleton contained in the material also makes the grouting material have excellent anti-creep performance, high temperature resistance, aging resistance, acid and alkali corrosion resistance and other excellent properties, and has good water flow sealing effect.

[0038] The above examples only express the preferred embodiments of the application, and the description is more specific and detailed, but it cannot be understood as a limitation on the scope of the patent of the application. It should be pointed out that for ordinary skilled persons in the art, without departing from the concept of the application, a number of modifications, improvements and substitutions can be made, which are all within the protection scope of the application.

Claims

1. A dam leakage treatment self-repairing high polymer grouting material, characterized in that: The A component resin and the B component; The A component comprises 40-60 parts of asphalt, 10-20 parts of aromatic oil for environment-friendly rubber, 8-20 parts of rosin polyester polyol, 20-40 parts of polyphenylmethane polyisocyanate, 0.1-1 part of catalyst, and 5-15 parts of auxiliary agent. The B component is a curing agent. The A component resin further comprises 1.5-6.5 parts of isocyanate polar groups. When the material is cracked by disturbance, the exposed isocyanate polar groups in the A component can react with water and self-polymerize to form a three-dimensional network structure, realizing continuous self-repairing and plugging.

2. The dam leak remediation self-healing high polymer grout material according to claim 1, characterized in that: The preparation steps of the A component resin comprise: Step S1, the asphalt and the aromatic oil for environment-friendly rubber are added into a clean vacuum reaction kettle, heated to 120℃, vacuumized for 2h, and the moisture in the reaction kettle is removed, and when the moisture is below 0.001%, the vacuumization is stopped; Step S2, the reaction kettle is cooled to 80℃, and then the rosin polyester polyol and the polyphenylmethane polyisocyanate are added into the reaction kettle, and fully stirred and mixed; Step S3, the catalyst is gradually added into the reaction kettle by using a peristaltic pump, and the auxiliary agent is added at the same time, and the temperature is kept at 80℃, and then the reaction is carried out for 2h under stirring, forming a repairing product, Step S4, the repairing product is packaged and stored under nitrogen condition.

3. The dam leakage treatment self-repairing high polymer grouting material according to claim 1, characterized in that: The catalyst is dibutyl tin dimethyl silicate.

4. The dam leak remediation self-healing high polymer grout material of claim 1, wherein: The curing agent is a trimerization catalyst.

5. The dam leak remediation self-healing high polymer grout material of claim 1, wherein: The asphalt has a penetration of 180-280 (0.1mm) (100g, 5s, 0℃), a softening point of ≥17℃, and a flash point of ≥210℃.

6. The dam leak remediation self-healing high polymer grout material of claim 1, wherein: The aromatic oil for environment-friendly rubber has an open flash point of ≥200℃, an aromatic hydrocarbon content of >84%, and a pour point of ≥10℃.

7. The dam leak remediation self-healing high polymer grout material of claim 1, wherein: The rosin polyester polyol has a hydroxyl value of 350-450mgKOH / g and a viscosity of 5000-12000mPa·s.

8. The dam leak remediation self-healing high polymer grout material of claim 1, wherein: The mass ratio of the A component resin and the B component is 100:0.05-0.

1.

9. A method for treating a dam seepage by using the self-repairing high polymer grouting material according to claim 2, characterized in that: The steps are as follows: Step one, the A component resin is put into a batching tank, heated to 120℃, and then the B component is added into the batching tank, and after stirring and mixing, a repairing liquid is obtained; Step two, the repairing liquid mixed in step one is injected into the concrete crack by using a grouting machine.